Guidelines for mono, double and triple antithrombotic therapy. Issue 1153 (13th January 2021) - van Uden, Renate C A E; Houtenbos, Ilse; Griffioen-Keijzer, Anita; Odekerken, Diego A M; van den Bemt, Patricia M L A; Becker, Matthijs L
ABSTRACT: Guidelines for antithrombotic therapy are complex, especially if a patient has several indications that require antithrombotic therapy. In general, no patient should receive lifelong double or triple antithrombotic therapy. In this overview, we outline the most common indications for mono, double and triple antithrombotic therapy; the preferred antithrombotic therapy and the recommended duration of therapy. Both antiplatelet therapy and therapeutic anticoagulation therapy with vitamin K antagonists or direct oral anticoagulants were included. European guidelines were used or, if no European guidelines were available, the Dutch guidelines were used.